NH4+ Association and Proton Transfer Reactions With a Series of Organic Molecules - Canaval, Eva; Hyttinen, Noora; Schmidbauer, Benjamin; Fischer, Lukas; Hansel, Armin (Frontiers in Chemistry, 2019)
In this study, we present reactions of NH4+ with a series of analytes (A): acetone (C3H6O), methyl vinyl ketone (C4H6O), methyl ethyl ketone (C4H8O) and eight monoterpene isomers (C10H16) using a Selective Reagent Ionization Time-of-Flight Mass Spectrometer (SRI-ToF-MS). We studied the ion-molecule reactions at collision energies of 55 meV and 80 meV. The ketones, having a substantially lower proton affinity than NH3, produce only cluster ions NH4+(A) in detectable amounts at 55 meV. At 80 meV, no cluster ions were detected meaning that these adduct ions are formed by strongly temperature dependent association reactions. Bond energies of cluster ions and proton affinities for most monoterpenes are not known and were estimated by high level quantum chemical calculations. The calculations reveal monoterpene proton affinities, which range from slightly smaller to substantially higher than the proton affinity of NH3. Proton affinities and cluster bond energies allow to group the monoterpenes as a function of the enthalpy for the dissociation reaction . We find that this enthalpy can be used to predict the NH4+-A cluster ion yield. The present study explains product ion formation involving NH4+ ion chemistry. This is of importance for chemical ionization mass spectrometry (CIMS) utilizing NH4+ as well as NH4+(H2O) as reagent ions to quantitatively detect atmospherically important organic compounds in real-time.